Pertumbuhan populasi pakan alami alona sp. pada media kultur dengan konsentrasi ragi berbeda - Pangandaheng, Agreystin; Pangkey, Henneke; Lantu, Sartje; Mingkit, Winda M.; Mokolensang, Jeffrie F.; Wulur, Stenly (e-Journal BUDIDAYA PERAIRAN, 2020)
The goal of this research was to observe the effects of yeast on the density rate of Alona sp. with various concentrations compared to the density rate in horse manure media. The treatments are as follows, treatment A yeast 30 mg yeast/0.5 L water, treatment B yeast 10 mg yeast/0.5 L water, treatment C yeast 5 mg yeast/0.5 L water, treatment D yeast 1 mg yeast/0.5 L water, treatment E 0.5 L well water, treatment F horse manure media (horse manure 10 gr, soil 50 g in 0.5 L water). The research was carried out for two weeks, and the density calculation was done once a week. The results obtained based on Anova One Way analysis are that yeast with different concentrations does not have a significant effect on the density of Alona sp. Nevertheless, it was concluded that the giving of yeast to Alona sp. is much more efficient and effective compared to horse manure media, because it is more hygienic, easy to obtain and not expensive, also from nutritional value, yeast has a higher value compared to horse manure media. The measuring of water quality parameter during the research was temperature around 26-30Â°C.